Liver disease in pregnancy. Issue 9 (13th July 2020) - Sasamori, Yukifumi; Tanaka, Atsushi; Ayabe, Takuya
Abstract : Development of liver diseases during pregnancy is not uncommon. They are caused by either a disorder that is unique to pregnancy or an acute or chronic liver disease that already exists or coincidentally develops as a comorbidity of pregnancy. Liver diseases unique to pregnancy include hyperemesis gravidarum; hypertensive disorders of pregnancy, such as pre‐eclampsia/eclampsia; hemolysis, elevated liver enzymes, and low platelet count syndrome; intrahepatic cholestasis of pregnancy; and acute fatty liver of pregnancy. Chronic liver diseases that affect pregnancy, or are affected by pregnancy, mainly include autoimmune liver diseases and non‐alcoholic fatty liver disease. Prompt diagnosis and management of liver diseases in pregnancy, while very challenging, is extremely important, as they might cause adverse maternal and fetal outcomes. Therefore, a multidisciplinary, collaborative approach involving both hepatologists and obstetricians is required. In this review article, the up‐to‐date epidemiology, etiology, clinical features, and outcomes of liver diseases in pregnancy are discussed, to promote a deeper understanding among physicians, and subsequently improved outcomes.